Christian remnant-African folk church : Seventh-Day Adventism in Tanzania, 1903-1980 - Höschele, Stefan. (Studies in Christian Mission, 2007)
The growth of Christianity in Africa during the twentieth century is one of the most fascinating shifts in the history of religions. This book presents a history of the Tanzanian Seventh-day Adventist Church, which is representative of this shift in many respects: slow beginnings, struggles over cultural issues, the emergence of a unique church life combining denominational heritage and African elements, frictions with governments, and the development of popular theology. Yet Tanzanian Adventism also exemplifies an important phenomenon which has been given little attention so far - the transformation of minority denominations to dominant religions. This study breaks new ground in analyzing how the Adventist "remnant" developed into an African "folk church" while attempting to remain true to its original ethos.